2007
DOI: 10.1093/rheumatology/kem221
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of etanercept and infliximab for the treatment of patients with psoriatic arthritis

Abstract: Only results for etanercept remained within the range of cost-effectiveness estimates considered to represent value for money in the NHS by the National Institute for Health and Clinical Excellence. Further research appears most valuable in relation to the short-term effectiveness, utility parameters and assumptions regarding the effect of rebound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 36 publications
2
57
0
3
Order By: Relevance
“…Previously costeffectiveness models of biologicals assumed linear relationship between functional status (HAQ) and direct costs in PsA based on RA data [12][13]. Huscher et al [4] confirmed this relation of total costs based on a PsA study and our results pointed out the same with HAQ.…”
Section: Discussionsupporting
confidence: 82%
“…Previously costeffectiveness models of biologicals assumed linear relationship between functional status (HAQ) and direct costs in PsA based on RA data [12][13]. Huscher et al [4] confirmed this relation of total costs based on a PsA study and our results pointed out the same with HAQ.…”
Section: Discussionsupporting
confidence: 82%
“…The increase of the antigen -"antigen rebound" -has been sparsely studied and only anecdotal reports exist in the literature. For example, rebound symptoms have been reported on cessation of anti-tumour necrosis factor (TNF) therapies (Bravo Vergal et al, 2007) and a corresponding increase in TNF levels have been demonstrated to occur in patients (Bhatia and Kast, 2007). Similarly, treatment with an anti-IL6 antibody has also been shown to increase total IL6 activity (Klein et al, 1995) and an increase in tumour size on cessation of VEGF treatment has also been reported (Cacheux et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several cost analysis studies have implied cost-effectiveness of anti-TNF therapies in AS and PsA patients with moderate to severe disease. [133][134][135][136] However, there have been no headto-head pharmacoeconomic studies of etanercept in comparison with other biologic therapies or traditional DMARDS. Furthermore, it is very diffi cult to estimate cost-effectiveness of long-term therapies in chronic diseases, with short-term data often having to be mathematically modeled over a patient's lifetime.…”
Section: Patient Focused Perspectivesmentioning
confidence: 99%
“…138 In a mathematical model investigating the cost-effectiveness of both etanercept and infl iximab for the treatment of active PsA from a UK National Health Service perspective, only etanercept was found to be potentially cost-effective over a 10-year and lifetime horizon. 135 In a cost evaluation study of 107 PsA patients from Italian rheumatology clinics who were unresponsive to DMARD therapy and treated with TNF antagonists (87% etanercept) for 12 months, there was a 97% likelihood that anti-TNF therapy would be considered cost effective at the willingness to pay threshold of €60,000 per QALY gained. 136 Therefore, based on currently available pharmacoeconomic data, one can speculate that over time, that the indirect and direct cost savings including a reduced need for joint replacement surgeries, decreased health care utilization, diminished need for other medications and therapies, improved quality of life, decreased work disability, and increased life expectancy in AS and PsA patients could be substantial.…”
Section: Patient Focused Perspectivesmentioning
confidence: 99%